OPTIMALIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGY MEDIA BASED ON INFOCUS ON LEARNING MOTIVATION OF GRADE VII STUDENTS OF SMP NEGERI 13 CILEGON - Dewi Kurniasih; Desty Endrawati Subroto; Kurniati Rahmadhani (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to determine whether the use of Infocus media has an effect on the learning motivation of Grade VII students in SMP Negeri 13 Cilegon City. This causes problems with students' learning motivation. Based on initial observations, there are problems in class VII of SMPN 13 Cilegon City, namely (1) students who are not interested in the learning process (2) less interested in learning, so that students have difficulty understanding the material presented by the teacher (3) Shiva from the material feels boring because the teaching used is only focused on book sources. This type of research is quantitative descriptive research. The population in this study was Grade VII students with a total of 106 in SMPN 13 Cilegon City. The data collection technique in this study is a questionnaire with a Likert scale with 5 alternative answers. With table results greater than 0.468, construct validity test was used and 21 questionnaires were declared valid. Meanwhile, reliability test used Cronbach Alpha formula with results of 0.786 for Infocus media variable and 0.733 for student learning motivation variable, data analysis used simple linear regression formula. The results of the study show that students are motivated to learn using Infocus-based information technology learning media with survey results above 50%. Hence, hypothesis h1 is accepted in this study. Based on the results of the above study, it can be concluded that (1) Infocus LCD Media can increase the learning motivation of students in SMPN 13 Cilegon City and (2) the use of Infocus LCD Media has an effect on students' learning motivation. SMPN 13 Cilegon City.